2018
DOI: 10.1186/s12913-017-2821-z
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative exploration of the discharge process and factors predisposing to readmissions to the intensive care unit

Abstract: BackgroundQuantitative studies have demonstrated several factors predictive of readmissions to intensive care. Clinical decision tools, derived from these factors have failed to reduce readmission rates. The purpose of this study was to qualitatively explore the experiences and perceptions of physicians and nurses to gain more insight into intensive care readmissions.MethodsSemi-structured interviews of intensive care unit (ICU) and general medicine care providers explored work routines, understanding and perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
(34 reference statements)
0
12
0
Order By: Relevance
“…These challenges, which was also described in our results, could indicate that an improvement in written communication and better communication tools among health care services could reduce hospital readmissions. Still, the hospital discharge process is often executed under time pressure, leading to lack of time to provide proper HSS and adequate information to the receiving healthcare agency [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…These challenges, which was also described in our results, could indicate that an improvement in written communication and better communication tools among health care services could reduce hospital readmissions. Still, the hospital discharge process is often executed under time pressure, leading to lack of time to provide proper HSS and adequate information to the receiving healthcare agency [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hospital readmissions, hospital discharges and transitional care have previously been well investigated. However, most of the research have separated the three entities, and examined them at each level of the healthcare service 20–23. For example, factors affecting hospital readmissions have been explored within the realm of primary healthcare services (eg, nurse turnover, nurse staffing and performance and care quality)24–26 or secondary healthcare services (eg, staff responsiveness, length of stay and medication-related events) 27–29…”
Section: Introductionmentioning
confidence: 99%
“…Missing data were then imputed via multivariate imputation (20), with a Bayesian ridge regression as the estimator (21). We used a similar outcome definition to by Lin et al (12), where positive cases were regarded as the ones where the patients could benefit from a prediction of readmission before being transferred or discharged: patients who were transferred or discharged but returned to ICU or died before a defined time limit (3,7,15 or 30 days).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown that readmission in the intensive care unit (ICU) is associated with poor clinical outcomes, increased length of ICU and hospital stay, and high costs (1, 2). One of the main reasons for ICU readmission that has been identified is premature discharge (3); in fact the transfer of patients from an ICU to a general hospital ward represents a high-risk event, and thus the decisions about which patients are ready to be discharged are daily struggles for ICU clinicians (4). Other studies have shown that determining the best timing for ICU discharge is usually based on subjective intuitions and that readmission prediction tools can help physicians in this endeavor, provided their performance and ease of adoption (5, 6).…”
Section: Introductionmentioning
confidence: 99%